2005
DOI: 10.1681/asn.2005010076
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Dimethylarginine Predicts Progression to Dialysis and Death in Patients with Chronic Kidney Disease

Abstract: High plasma asymmetrical dimethylarginine (ADMA) signals endothelial dysfunction and atherosclerosis in the general population and predicts mortality in ESRD. The relationship among plasma levels of ADMA, renal function, and the risk for progression to ESRD (halving GFR or dialysis start) and death in an incident cohort of 131 patients with chronic kidney disease was investigated. Cox's competing risk regression was used to model double-failure times (progression to ESRD and death) as a function of ADMA. Covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
250
3
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(277 citation statements)
references
References 33 publications
16
250
3
8
Order By: Relevance
“…Zoccali et al reported for the first time that plasma ADMA concentration was a strong and independent predictor of overall mortality and cardiovascular outcomes in a cohort of 225 hemodialysis patients (17). In addition, they found that plasma ADMA concentration was inversely related to GFR and that it positively correlated with progression to ESRD and future mortality in 131 patients with mild to advanced CKD (13). In a prospective study Lajer et al reported that plasma ADMA levels pre- dicted the development of future fatal and nonfatal cardiovascular events as well as a rapid decline in GFR in a cohort of 397 type 1 diabetes patients with overt diabetic nephropathy as well as in 175 patients with persistently normal albuminuria after long-term follow-up for 11.3 years (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoccali et al reported for the first time that plasma ADMA concentration was a strong and independent predictor of overall mortality and cardiovascular outcomes in a cohort of 225 hemodialysis patients (17). In addition, they found that plasma ADMA concentration was inversely related to GFR and that it positively correlated with progression to ESRD and future mortality in 131 patients with mild to advanced CKD (13). In a prospective study Lajer et al reported that plasma ADMA levels pre- dicted the development of future fatal and nonfatal cardiovascular events as well as a rapid decline in GFR in a cohort of 397 type 1 diabetes patients with overt diabetic nephropathy as well as in 175 patients with persistently normal albuminuria after long-term follow-up for 11.3 years (21).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma ADMA level has been associated with endothelial dysfunction (7,9) and was observed in patients with various risk factors for atherosclerosis as well as CKD (10,11). Several studies have shown that plasma ADMA level may predict the progression of renal injury in patients with early-stage CKD (12,13). In addition, high plasma ADMA level has been reported to be an independent risk factor for cardiovascular disease and allcause mortality in a community-based population (14), in patients with coronary artery disease (CAD) (15,16), and in patients with ESRD (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study examined only CVD death as an outcome; however, individuals with CKD are at high risk of all-cause mortality and this competing risk my obscure statistically significant risk factors. 21,22 An examination of the ARIC cohort by Muntner et al evaluated 391 individuals with CKD at baseline, and, in order to increase power, analyzed an additional 416 individuals who had developed CKD at the time of their second evaluation. 7 In multivariable analyses, increased waist circumference, apolipoprotein B, fibrinogen, anemia, and reduced albumin were all associated with cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin 18, an epithelial-specific cytoskeletal protein released into urine or serum upon tubular cell death, might also be a novel marker of CKD (395). Several other molecules are under investigation as biomarkers in CKD, including asymmetric dimethylarginine, an endogenous inhibitor of NO synthase (396), Creactive protein (CRP), tumor necrosis factor receptor (TNF-R) II, pentraxin-3, adiponectin and apolipoprotein A-IV, as metabolic factors involved in the regulation of kidney metabolism, or endostatin as an anti-angiogenic factor (396,397). In kidney allografts, increased urinary CCL-2 was associated with renal fibrosis (317).…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%